An assessment of the impact of training and development on staff efficiency and service delivery in urban municipalities: The case of Chitungwiza municipality, 2013 to 2016. - Shayamano, Melody (Midlands State University, 2020)
This study was aimed at assessing the impact of training and development of staff efficiency and service delivery in urban municipalities with specific reference towards CM from 2013 to 2016. The study utilised a mixed method approach encompassing both qualitative and quantitative data analysis with a case study design. The sample study was selected from the employees within Chitungwiza using stratified random sampling as well as judgemental sampling. The research study utilised both primary sources (questionnaires, interviews, photographs and observations) and secondary sources (books, government documents, the internet, articles and journals). A conceptual organisational learning theory was employed to explain the benefits associated with training and development from an individual, group and organisational perspective. Data was analysed with the use of SPSS package and excel package to deduce quantitative data and qualitative data was analysed with the use of thematic data analysis and the use of pictures. The study showed a myriad of weaknesses and strengths of employees at Chitungwiza Municipality in the conduct of their duties. Basically, the study showed that much of the woes being experienced at the Municipality in as much as service delivery is concerned are mostly attributed to poor utilisation of the employees other factors such as autocracy, bureaucracy, lack of independency, corruption and lack of employee motivation were also highlighted contributing to poor service provision at the Municipality from 2013 to 2016. It was recommended that the Municipality should prioritise and value their employees that will go a long way in motivating them to be more efficient and effective in conducting their duties of which all this can be addressed with proper and frequent training and development programmes of the staff to meet with the dynamic global community.